(3-4)-(2+4*3)=-6+5*3

Simple and best practice solution for (3-4)-(2+4*3)=-6+5*3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3-4)-(2+4*3)=-6+5*3 equation:


Simplifying
(3 + -4) + -1(2 + 4 * 3) = -6 + 5 * 3

Combine like terms: 3 + -4 = -1
(-1) + -1(2 + 4 * 3) = -6 + 5 * 3
-1 + -1(2 + 4 * 3) = -6 + 5 * 3

Multiply 4 * 3
-1 + -1(2 + 12) = -6 + 5 * 3

Combine like terms: 2 + 12 = 14
-1 + -1(14) = -6 + 5 * 3

Multiply -1 * 14
-1 + -14 = -6 + 5 * 3

Combine like terms: -1 + -14 = -15
-15 = -6 + 5 * 3

Multiply 5 * 3
-15 = -6 + 15

Combine like terms: -6 + 15 = 9
-15 = 9

Solving
-15 = 9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 1.5x-3=12 | | 11+8x=01 | | 54-3x=x^2 | | -4(x-5)+2=-20x+22 | | 3(3+4)=3*3+4 | | -8(m-5)=25-5m | | (3)(4)(x)=6 | | 8mx(4m+1)=170 | | -6b(5a-2b)-7(-3ab-4b^2)= | | 45q-32=70q-82 | | a+18=23 | | -2x-6=2-4x-(-x-1) | | (G+8)=2X+H | | 11(x-5)=(x+5) | | -21=2x-9 | | 191-v=89 | | -3(r+6)=-58 | | 3x+2=3(4)+2 | | 4y-4=35-6y | | z^4=28+96i | | 2x-18=3x+8 | | 231=165-y | | x=-12+-3y | | 10G+1=2k+(7X+Y) | | 5r+5-r-5= | | -3.8y=-24 | | 3(3+4)=3x+4 | | 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) |

Equations solver categories